2019
DOI: 10.3145/epi.2019.mar.19
|View full text |Cite
|
Sign up to set email alerts
|

The narratives of fertility clinic’s websites in Spain

Abstract: One of the important developments in assisted reproductive technology is the technique of oocyte preservation, which enables women to preserve their eggs when there is a threat of becoming infertile in the future. In spite of the still experimental status of this procedure, fertility clinics widely recommend it to healthy women who wish to postpone childbearing for social reasons. Since in fertility clinic's websites appear extensive recommendations and promotion about this technology, it seems important to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“… 46 , 47 In some cases, information on treatments and success rates was considered misleading and was found to aggressively market some ART procedures, 48 including non-medical EF. 49 Our findings provide further evidence of the need to improve the quality of the resources on fertility and fertility preservation.…”
Section: Discussionsupporting
confidence: 55%
“… 46 , 47 In some cases, information on treatments and success rates was considered misleading and was found to aggressively market some ART procedures, 48 including non-medical EF. 49 Our findings provide further evidence of the need to improve the quality of the resources on fertility and fertility preservation.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies regarding information on infertility and fertility in the media have examined (1) newspaper reports about assisted reproductive technology [ 35 ]; (2) information on clinic websites [ 36 ]; (3) the readability, suitability, and quality of online information [ 32 , 37 ]; (4) online videos made by laypersons and informational infertility-related educational videos [ 38 ]; and (5) online emotional support and social media on infertility-seeking to reduce isolation [ 39 , 40 ]. As mentioned above, although people who are trying to conceive tend to have relatively low levels of knowledge about lifestyle factors associated with reduced fertility, especially male infertility, to our knowledge, few studies have investigated the content of online information on the lifestyle factors associated with reduced fertility.…”
Section: Introductionmentioning
confidence: 99%
“…They choose to freeze their eggs because of a variety of reasons, important among them the physical, economical, structural, and personal factors. Indeed, it was found that women chose to freeze eggs because of the absence of conditions crucial for pursuing motherhood, and not because of the presence of any dominant reasons [62]. Interestingly, there have been investigations into fertility preservation and the attitudes surrounding it in several countries [69][70][71][72][73][74].…”
Section: Individual Patient's Beliefs Perception and Opinionsmentioning
confidence: 99%